Mediation of Purchase Interest: The Influence of Price, Product Quality and Social Media Promotion on The Purchase Decision of AMDK in Bondowoso Regency - Rolis Wikarsono; Budi Santoso; Nurul Qomariah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of price, product quality, social media promotion, and purchase interest on the purchase decision of A3 Fresh O2 products in Bondowoso Regency, as well as examine the role of purchase interest as an intervening variable. The research method used is quantitative with a survey approach, purposive sampling, and data analysis using the Partial Least Square (PLS) technique. The results of the study show that price, product quality, and social media promotions have a positive and significant effect on consumer purchase decisions, respectively. In addition, these three variables also have a positive and significant effect on purchase interest, while purchase interest directly influences purchasing decisions significantly. The mediation analysis confirmed that purchase interest strengthened the influence of price, product quality, and social media promotion on the purchase decision of A3 Fresh O2 products. These findings recommend the integration of pricing strategies, improving product quality, and optimizing digital promotions with the right purchase interest to improve purchasing decisions, sales volume, and purchase loyalty in the Bondowoso bottled water market.